2012
DOI: 10.1007/s00424-012-1178-8
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of smooth muscle caldesmon affects the relaxation kinetics of arterial muscle

Abstract: Smooth muscle caldesmon (h-CaD) is an actin- and myosin-binding protein that reversibly inhibits the actomyosin ATPase activity in vitro. To test the function of h-CaD in vivo, we eliminated its expression in mice. The h-CaD-null animals appeared normal and fertile, although the litter size was smaller. Tissues from the homozygotes lacked h-CaD and exhibited up-regulation of the non-muscle isoform, l-CaD, in visceral, but not vascular tonic smooth muscles. While the Ca2+-sensitivity of force generation of h-Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 70 publications
1
23
3
Order By: Relevance
“…It is interesting to contrast the findings reported here with several other smooth muscle-restricted actin-binding proteins that are dispensable for similar functional activity in these organs, including CNN1 (17,36), TAGLN (37), CSRP1 (38), and CALD1 (39), which would suggest that compensatory pathways exist to preserve normal organ function in the absence of each of these actin-binding proteins. On the other hand, genetic inactivation of Myh11, encoding the major thick filament protein in smooth muscle, leads to megacystis, a decrease in intestinal motility, defective contraction of the bladder, and early postnatal death, all of which are reminiscent of the Lmod1 −/− phenotype and human MMIHS (40).…”
Section: Discussioncontrasting
confidence: 56%
“…It is interesting to contrast the findings reported here with several other smooth muscle-restricted actin-binding proteins that are dispensable for similar functional activity in these organs, including CNN1 (17,36), TAGLN (37), CSRP1 (38), and CALD1 (39), which would suggest that compensatory pathways exist to preserve normal organ function in the absence of each of these actin-binding proteins. On the other hand, genetic inactivation of Myh11, encoding the major thick filament protein in smooth muscle, leads to megacystis, a decrease in intestinal motility, defective contraction of the bladder, and early postnatal death, all of which are reminiscent of the Lmod1 −/− phenotype and human MMIHS (40).…”
Section: Discussioncontrasting
confidence: 56%
“…The exact role of CaD in the regulation of contraction can be better understood using smooth muscle that lacks whole CaD or a selected functional domain of CaD. Ablation of smooth muscle CaD (h-CaD) in a previous study showed overexpression of nonmuscle CaD (l-CaD), and while the Ca 2ϩ sensitivity of force generation of h-CaD-deficient smooth muscle remained largely unchanged, the kinetic behavior during relaxation in arteries was different (20).…”
Section: Discussionmentioning
confidence: 98%
“…It is generally believed that CaD promotes relaxation [28, 29]. Albrecht et al [28], demonstrated that exogenous addition of CaD to permeabilized tissues accelerates their rate of relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies reported that CaD accelerates the rate of smooth muscle relaxation and suggested that this is accomplished by inhibiting the cooperative reattachment of dephosphorylated myosin [28, 29]. In the current study, we investigated at the molecular level, the role of CaD in the binding of unphosphorylated myosin to actin.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation